Job insecurity and subjective sleep quality: The role of spillover and gender. (13th August 2020) - Kim, Yun‐Kyoung; Kramer, Amit; Pak, Sunjin
Abstract: Perceived job insecurity is a critical job stressor that creates the conditions for negative health and performance outcomes for workers while potentially increasing health‐related costs for employers. Sleep quality, an important proxy of health, has been understudied in relation to the impact of perceived job insecurity. Using job stress concepts and a perseverative cognition model, this study examines the association between perceived job insecurity and subjective sleep quality while considering negative work spillover as a mediator. We expand our analysis to consider gender as a moderator of the job insecurity–sleep quality relationship, predicting the relationship will be stronger for men than for women. Study 1 uses a nationally representative sample from the Midlife Development in the United States National Survey Refresher study consisting of 1031 working adults and a multi‐group path analysis to test our hypotheses. Results show that negative work spillover mediates the relationship between perceived job insecurity and subjective sleep quality. Study 2 uses a sample of 152 working adults who participated in three biweekly surveys. The mediating role of negative work spillover is replicated in Study 2. In both studies, no gender moderation is found. Theoretical and methodological contributions, limitations and future research directions are discussed.